Relationship between locus of control and connectedness with prosocial behavior among the adolescents in Kuala Lumpur, Malaysia - Lau, Yee Ching (2013)
The current study examined the relationships between locus of control and connectedness with adolescents’ prosocial. The study also determined the moderation effect of age on the relationship between the independent and dependent variables. Social cognitive theory was used to guide the study. A multiple stage sampling method was used to select 384 respondents aged 13 to 16 (mean= 14.52 years; s.d.= 1.16) from four secondary schools in Kuala Lumpur. Self-administered questionnaire with 3 main instruments which are Prosocial Behavior TendenciesRevised by Carlo, Hausmann, Christiansen and Randall (2003), The Child NowickiStrickland Internal-External Scale (CNS-IE) by Nowicki and Strickland (1971) and The Hemingway: Measure of Adolescent Connectedness by Karcher (2002) were used to measure prosocial behavior, locus of control, and connectedness respectively. Independent sample T-test, one-way ANOVA, Pearson Correlation and multiple regression were used to answer the research questions respectively. A significant level of 0.05 errors was used for the hypothesis testing. Results revealed that there is no significant gender difference in prosocial behavior however, there was a significant age difference (F=10.32) in prosocial behavior. Results also showed that there are significant relationships between locus of control (r=-.233),family connectedness (r=.396), academic connectedness (r=.576) and social connectedness (r=.505) with prosocial behavior. Age, academic connectedness and social connectedness were the unique predictors of prosocial behavior (Beta=1.34, .393, .308). Results showed that there is moderation effect of age in relationship between academic connectedness and prosocial behavior. The findings support to the theory of Bandura (1963) in that prosocial behavior can be influenced by personal and environmental factors.